2004
DOI: 10.1007/s10499-004-8528-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of reciprocating flow versus constant flow in an integrated, gravel bed, aquaponic test system

Abstract: Murray cod, Maccullochella peelii peelii, and Green oak lettuce, Lactuca sativa, were used to test for differences between two aquaponic flood regimes; reciprocal flow (hydroponic bed was periodically flooded) and constant flow (hydroponic bed was constantly flooded), in a freshwater aquaponic test system, where plant nutrients were supplied from fish wastes, while plants stripped nutrients from the wastewater before it was returned to the fish. The Murray cod had FCRs and biomass gains that were statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 11 publications
1
30
2
Order By: Relevance
“…Nitrite-N concentration also did not show any significant variation but showed slight reduction with increase of water circulation. Lennard and Leonard (2004) in their comparative studies of reciprocating flow versus constant flow in an integrated-gravel bed-aquaponics system showed that constant flow treatment appear to remove more nitrate from culture waters than did reciprocating control treatments, but no significant differences was detected. Nitrate-N concentration of water, which is relatively harmless to fishes, was also found to be in the favourable range in all treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrite-N concentration also did not show any significant variation but showed slight reduction with increase of water circulation. Lennard and Leonard (2004) in their comparative studies of reciprocating flow versus constant flow in an integrated-gravel bed-aquaponics system showed that constant flow treatment appear to remove more nitrate from culture waters than did reciprocating control treatments, but no significant differences was detected. Nitrate-N concentration of water, which is relatively harmless to fishes, was also found to be in the favourable range in all treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the hydroponic surface/fish tank volume ratio from 0.67 to 2.25 augmented the daily water replacement from 1.2% to 4.7% (McMurtry et al, 1997b). Lennard and Leonard (2005) measured an average daily consumption of 2.65% in an AP system with a medium-based hydroponic bed planted with L. sativa for 21 days and observed no influence of the management of the hydroponic section (reciprocating flood/drain cycle vs. constant flow) on the water. Also, the type of hydroponics (gravel, floating or NFT) had no influence on water loss (Lennard and Leonard, 2006) (Table 2).…”
Section: Water Consumptionmentioning
confidence: 90%
“…In both, the removal of nutrients and/or pollutants is complex and depends on a variety of mechanisms, including sedimentation, filtration, precipitation, volatilisation, adsorption, plant uptake, and various microbial processes (Wießner et al, 2005;Vymazal, 2007;Wu et al, 2014;Barbera et al, 2015;Maucieri et al, 2014Maucieri et al, , 2016. Lennard and Leonard (2005) compared a reciprocating flood/drain cycle (10 min flood every 70 min) to a constant flow in a hydroponic gravel bed (0.52 m 2 ) plated with lettuce during 21-day cycle. They obtained significantly higher lettuce yield (resulting in higher nitrate and phosphate assimilation), better pH buffering and higher dissolved oxygen concentrations in the constant flow.…”
Section: Continuous Flow Vs Intermittent Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have shown that high PH plants display nutrient deficiencies and on contradiction, low PH ammonia accumulates to toxic levels for fish [10], [11], [12] and [3].…”
Section: Introductionmentioning
confidence: 99%